The Effects of a Social Support Program on the Loneliness and Well-being of Older Persons - Tingchum, Phatcharaphon; Changmai, Sakul; Toskulkao, Tipa (Nursing Journal of The Ministry of Public Health, 2022)
This quasi-experimental study using a two-group pretest-posttest design aimed to investigate the effects of a social support program on loneliness and well-being of older persons. The subjects were 60 older persons aged 60 and over, who met the inclusion criteria. Convenience sampling was used to recruit samples, while drawing was used to assign each person to be in the experimental group (n=30) or the control group (n=30). The experimental group participated in a five-week social support program that was developed based on the Schaefer’s concepts of social support, while the control group received regular care activities.The research instruments were the social support program validated by five experts. The loneliness questionnaire and the well-being questionnaire were tested for reliability with Cronbach’s alpha coefficients of .80 and .82, respectively.The data were analyzed using descriptive statistics, paired t-tests, and independent t-tests.The results of the study were as follows. After participation in the social support program, the mean score for loneliness in the experimental group was lower than the pre-test score and the mean score for well-being in the experimental group was higher than the pre-test score at statistical significance. The mean score for loneliness in the experimental group after participating in the social support program was statistically significantly lower after participation in the social support program than in the control group, which received regular care activities. In addition, the mean difference in well-being scores was statistically significantly higher in the experimental group after participation in the social support program was higher than in the control group receiving regular care (p<.05). Based on the results of this research, the social support program reduced loneliness and increased well-being in older persons. Therefore, the social support program for older people should be promoted in other groups in order to reduce loneliness scale and increase their well-being.